Controlled image fusion - Montenegro Joo, Javier (2013)
A Virtual Lab to experiment on controlled fusion of two digital images has been developed. The resulting image has user pre-defined percentages of each contributing image. With the aim on improving the quality of the resulting image in the fusion, the Virtual Lab has been enabled with the option of selecting a color to be ignored during the fusion process, in this way this color is not fussioned. Successful experiments have been executed fusing three images using the same algorithm.